PENGARUH DUKUNGAN ORANG TUA DAN GENDER TERHADAP MOTIVASI BELAJAR SISWA KELAS IX SMP PGRI 8 DENPASAR - Dion Putra Sunyata; Ida Ayu Karina Adityanti Manuaba; I Gusti Agung Ayu Yunita Utami (Bajang Institute, 2026)
This study examined the extent to which parental support and gender influences the learning motivation of Grade IX students at SMP PGRI 8 Denpasar. The background of this research is that students learning motivation often becomes a complex issue influenced by various internal and external factors, including parental support and gender differences that shape how students engage in learning activities. Adopting a quantitative associative design, data were obtained from 100 students (51 girls, 49 boys) using two Likert-type instruments. Both measures satisfied reliability and validity requirements. After the assumptions of normality, linearity, and multicollinearity were met, multiple-linear regression in JASP showed that the overall model was significant (F < 0.001; R² = .25). Parental support emerged as the strongest predictor (β = 0.597, b = 0.382, p < 0.001), while gender also contributed significantly (β = 0.268, b = 5.401, p = 0.003), indicating that girls reported higher motivation than boys at comparable support levels. Follow-up simple regressions revealed that parental support explained 21% of the variance in intrinsic motivation and 52% in extrinsic motivation. The findings highlight the importance of meaningful parental involvement and gender-responsive strategies for enhancing students learning motivation.